Analisis naratif tindakan Yesus mengusir roh jahat di Gerasa dalam perspektif etika Utilitarianisme - Romasi Maska Hutagalung (Sekolah Tinggi Alkitab Penyebaran Injil (STAPIN) Majalengka, 2026)
The account of Jesus casting out Legion in Mark 5:1–20 is generally understood as a narrative of deliverance. However, Jesus' action, which resulted in the death of a herd of pigs, also raises ethical questions concerning its consequences for the various parties involved. This study aims to analyze the narrative through a dialogue between narrative criticism and utilitarian ethics. Employing a qualitative method with an interdisciplinary approach, the study uses narrative criticism to examine the narrative structure, characterization, conflict, and consequences of Jesus' action, while the principles of utility developed by Jeremy Bentham and John Stuart Mill are employed to evaluate those consequences from a utilitarian perspective. The findings reveal that Jesus' action generated significant utility for the individual who was restored, while simultaneously causing economic loss and rejection from the community. These findings suggest that utilitarianism helps explain the moral tension embedded in the narrative but is insufficient to fully account for the theological significance of Jesus' action, which centers on liberation, restoration, and the manifestation of the authority of the Kingdom of God.